DAMPAK PERGAULAN BEBAS SEBAGAI SUMBER IDE PENCIPTAAN KRIYA SENI - I Wayan Arissusila (Pascasarjana Universitas Hindu Indonesia, 2017)
Humans are God’ s creatures, who live according to their respective abilities. There are human lives prefer the pleasure, enjoyment and luxury. In life looks like a good meal, luxurious clothing and visible among adolescents tend to lead to sex. Adolescence is the age, studying opportunities and positive nature.In fact, many carried out by mutually couple, without thinking about the future and health. Such behavior is most likely caused by promiscuity impact of AIDS on the body including the organs that are inside, resulting in death. In this paper, the problem can be posed: how do mentranspormasi theme, theimpact of free associations as the source of the idea of creathing art craft. By using the methods associated with the stages of the creations of works of art. Used to dissect the problems that relepan theory with the creation of works of art. The result can be aware of the imfact of free association as a sourceof ideas in the creation of craft art, threedimensional shaped and finished to use transparent watercolors